Intermediate product regulation over tandem catalysts for one-pass conversion of syngas to ethanol. Issue 7 (26th February 2019) - Zhang, Yongkang; Ding, Chuanmin; Wang, Junwen; Jia, Yanming; Xue, Yanan; Gao, Zhiting; Yu, Bo; Gao, Bize; Zhang, Kan; Liu, Ping
Abstract : Selective conversion of syngas (CO/H2 ) to ethanol is an attractive but challenging target. Abstract : Selective conversion of syngas (CO/H2 ) to ethanol is an attractive but challenging target. Herein, a feasible ethanol synthesis route from syngas was reported over sandwich catalysts of CuZnO x and copper-modified H-MOR and CuZnO x, in which CO activation and carbonylation and hydrogenation processes are efficiently coupled under reaction conditions of 4.6 MPa and 200 °C. Specifically, H-MOR modified by different concentrations of copper nitrate (denoted as n CM, n denoting the concentration of copper nitrate) plays a vital role in the carbonylation process. The introduction of Cu species significantly enhances the ethanol selectivity from 2.56% to 15.62%. Moreover, in situ Fourier transform infrared (FT-IR) spectroscopy, adsorption of pyridine (Py-IR), CO temperature programmed desorption (CO-TPD), and X-ray photoelectron spectroscopy (XPS) indicated that the Cu cations preferentially replace the Brønsted (B) acid sites at the side pocket openings, and the specificity could cause migration of free Cu + during the reduction process. The reduction temperature not only affects the content of Cu + and Cu 0 but also affects their distribution in channels of n CM. The catalytic performance results implied that Cu + has a double-sided effect on ethanol synthesis: the good side is that the Cu + ions promote the carbonylation process by adsorbing and activating CO molecules, and the bad side is that the electrostatic interaction between Cu + and the acetyl cations might result in the conversion of the acetyl cations to ketenes. Essentially, acetyl and ketene were respectively considered as intermediates for the synthesis of methyl acetate (MA) and hydrocarbons.